Strategies for teaching and learning vocabulary - Teng, Feng (Beyond Words, 2014)
Abstract This article presents an overview of current research on second language vocabulary learning and proposes eight strategies for teaching and learning vocabulary. First, to facilitate effective vocabulary teaching, choosing high-frequency words is essential. Teachers of vocabulary also need to add explicit, intentional teaching to incidental learning. In addition, vocabulary learning strategies including morphological awareness and lexical inference provides a platform by which learners can improve both receptive and productive vocabulary knowledge. This article also suggests that productive vocabulary knowledge needs more attention than receptive vocabulary knowledge, and that available textbooks seldom address vocabulary sufficiently. In summary, it is very important for all learners and teachers to acknowledge that learning vocabulary is incremental in nature, and we should develop a principled, long-term program for teaching and learning vocabulary.